Serum IL-6 in combination with synovial IL-6/CRP shows excellent diagnostic power to detect hip and knee prosthetic joint infection - Gallo, Jiri; Svoboda, Michal; Zapletalova, Jana; Proskova, Jitka; Juranova, Jarmila (PloS one, 2018)
BACKGROUND: The diagnosis of prosthetic joint infection (PJI) is still a challenge in some patients after total joint replacement. Interleukin-6 (IL-6) strongly participates in the arrangement of the host-bacteria response. Therefore, increased levels of IL-6 should accompany every PJI. PURPOSE: The aim of the study was to show diagnostic characteristics of serum IL-6 for the diagnosis of prosthetic joint infection (PJI). We also compared the diagnostic values of serum IL-6 with synovial IL-6 (sIL-6) and synovial C-reactive protein (sCRP). STUDY DESIGN: We performed a prospective study of 240 patients in whom serum IL-6 was determined before total hip (n = 124) or knee (n = 116) reoperations. The PJI diagnosis was based on the MSIS (Musculoskeletal Infection Society) criteria (2011). Receiver operating characteristic plots were constructed for IL-6, sIL-6, and sCRP. RESULTS: PJI was diagnosed in 93 patients, and aseptic revision was diagnosed in 147 patients. The AUC (area under curve) for IL-6 was 0.938 (95% CI; 0.904-0.971). The optimal IL-6 cut-off value for PJI was 12.55 ng/L. Positive and negative likelihood ratios for IL-6 were 8.24 (95% CI; 4.79-14.17) and 0.15 (95% CI; 0.09-0.26), respectively. The optimal sIL-6 and sCRP cut-off values were 20,988 ng/L and 8.80 mg/L, respectively. Positive and negative likelihood ratios for sIL-6 were 40.000 (95% CI; 5.7-280.5) and 0.170 (95% CI; 0.07-0.417), respectively. Negative likelihood ratio for sCRP was 0.083 (95% CI; 0.022-0.314). CONCLUSIONS: The present study identified the cut-off values for serum/synovial IL-6 and synovial CRP for diagnostics of PJI at the site of THA and TKA and separately for each site. The diagnostic odds ratio for serum/synovial IL-6 and synovial CRP is very good. Simultaneous positivity of serum IL-6 either with synovial IL-6 or synovial CRP almost excludes false negative detection of PJI at the site of interest.
Keywords: Arthroplasty, Replacement, Knee; infekce spojené s protézou; ROC Curve; totální endoprotéza kolene; Humans; C-reaktivní protein; Arthroplasty, Replacement, Hip; Female; Aged; Interleukin-6; náhrada kyčelního kloubu; senioři; lidé; Prosthesis-Related Infections; Hip Prosthesis; Synovial Membrane; ženské pohlaví; synoviální membrána; Male; interleukin-6; protézy kolene; Aged, 80 and over; senioři nad 80 let; kyčelní protézy; ROC křivka; mužské pohlaví; C-Reactive Protein; Knee Prosthesis